2011
DOI: 10.1021/ie2001633
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bifunctional Ionic Liquid Extractants [A336][CA-12] and [A336][CA-100] to the Lanthanum Extraction and Separation from Rare Earths in the Chloride Medium

Abstract: In this Article, bifunctional ionic liquid extractants (Bif-ILEs) tricaprylmethylammonium sec-octylphenoxy acetic acid ) and tricaprylmethylammonium sec-nonylphenoxy acetic acid ([A336][CA-100]) used for the rare earths (REs) extraction from the chloride medium have been investigated. The effects of extractants concentration, equilibrium pH of aqueous phase, salt concentration, temperature, etc., were discussed. The results show that the extraction ability of [A336][CA-12] and [A336][CA-100] is higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 30 publications
3
49
0
6
Order By: Relevance
“…The extraction and separation of rare earth metals was examined by using these new compounds as extractants dissolved in organic solvents. It was reported that higher extraction ability was obtained for the bif-ILE than that for the mixture of two extractants that are the constituents of bif-ILE [68][69][70].…”
Section: Task-specific Ionic Liquidsmentioning
confidence: 99%
“…The extraction and separation of rare earth metals was examined by using these new compounds as extractants dissolved in organic solvents. It was reported that higher extraction ability was obtained for the bif-ILE than that for the mixture of two extractants that are the constituents of bif-ILE [68][69][70].…”
Section: Task-specific Ionic Liquidsmentioning
confidence: 99%
“…Alkyl‐phosphate has been widely used for many years in industrial processes such as solvent extraction, heavy metal ion reagent, plasticizer, lubricant, surfactant, corrosion inhibitor, etc . Tri‐n‐butyl phosphate (TBP) is one of the alkyl‐phosphates and has been used as an extractant in the PUREX process for the separation of uranium and plutonium from irradiated nuclear fuel over the last six decades .…”
Section: Introductionmentioning
confidence: 99%
“…The quaternary ammonium salt [A336]Cl is extensively used as a synergistic agent, often in combination with HTTA, for synergistic extraction of trivalent lanthanides [2,3], which has been found to be considerably enhanced relative to [A336]Cl salts or HTTA alone. Ammonium-Bif-ILEs containing 1,3-diketonate [19] anions [TTA]  have been reported for the extraction of plutonium(IV), but not for the extraction of REs(III) [20,21].…”
Section: Introductionmentioning
confidence: 99%